PENGARUH PENGGUNAAN APLIKASI PEMBELAJARAN ADAPTIF TERHADAP PENINGKATAN PRESTASI BELAJAR MAHASISWA PADA MATA KULIAH BAHASA INGGRIS DI INSTITUT TEKNOLOGI BISNIS AAS INDONESIA - Dewi Muliasari; Tino Feri Efendi (JURNAL ILMIAH EDUNOMIKA, 2023)
This research aims to investigate the effect of using adaptive learning applications on improving student learning achievement in English courses at the AAS Indonesia Institute of Business Technology. Adaptive learning applications are technologies that enable the delivery of learning materials tailored to the needs and level of understanding of individual learners. This research method uses an experimental design with a control group and a treatment group. The research sample consisted of two groups of students who enrolled in English courses in a particular semester. One group was given access to an adaptive learning application, while the control group used conventional learning methods. Learning achievement data was collected from the evaluation results of assignments, exams, and tests conducted during the research period. Statistical analysis was used to compare learning achievement results between the control and treatment groups after the learning period ended. The results of this study are expected to provide further understanding of the effectiveness of adaptive learning applications in improving student learning achievement in English courses. The implications of these findings can be an important reference for educational institutions and the development of adaptive learning technology in the future. Keywords Institut Teknologi Bisnis AAS Indonesia, adaptive learning, learning achievement, English, Institut Teknologi Bisnis AAS Indonesia.